2017
DOI: 10.1016/j.jsxm.2016.11.322
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Single-Treatment, Surface-Cooled Radiofrequency Therapy on Vaginal Laxity and Female Sexual Function: The VIVEVE I Randomized Controlled Trial

Abstract: Introduction Vaginal laxity is a highly prevalent and undertreated medical condition. Aim To evaluate the efficacy and safety of surface-cooled, monopolar radiofrequency (RFc) therapy for the treatment of vaginal laxity in the VIVEVE I trial. Methods The VIVEVE I trial was a prospective, randomized, single-blinded, and sham-controlled study. Nine study center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 24 publications
1
80
0
Order By: Relevance
“…This nonspecific definition underscores the heterogeneity of presentations among women complaining of this condition, as well as the unestablished correlation with other symptomatology. Indeed, most of the literature addressing the symptom of VL has focused on treatment modalities, nonsurgical and surgical, rather than on the clinical characteristics and coexisting conditions . The prevalence of VL has not been consistent across studies, ranging from 2% to 48% .…”
Section: Introductionmentioning
confidence: 99%
“…This nonspecific definition underscores the heterogeneity of presentations among women complaining of this condition, as well as the unestablished correlation with other symptomatology. Indeed, most of the literature addressing the symptom of VL has focused on treatment modalities, nonsurgical and surgical, rather than on the clinical characteristics and coexisting conditions . The prevalence of VL has not been consistent across studies, ranging from 2% to 48% .…”
Section: Introductionmentioning
confidence: 99%
“…The term VLS and therefore its therapy, vaginal rejuvenation, is not endorsed or formally defined by the leading gynecological societies . However, management of the symptoms have evolved from techniques involving sutures and the adaptation of traditional urogynecological procedures to the use of LASER and radiofrequency procedures …”
Section: Vaginal Laxity Syndromementioning
confidence: 99%
“…11 However, management of the symptoms have evolved from techniques involving sutures and the adaptation of traditional urogynecological procedures to the use of LASER 61,90 and radiofrequency procedures. [91][92][93][94][95][96][97][98][99] In 2011, there was an attempt to restore the rugae of the vagina in postmenopausal women ("vaginal rugation rejuvenation"), by vaporization of the vaginal wall in order to create parallel grooves. The procedure was performed in women with a sensation of a loose or smooth vagina.…”
Section: Grade Of Recommendationmentioning
confidence: 99%
“…Another study showed similar results lasting up to a year . One recently completed, randomized, sham‐controlled trial (NCT02261974) evaluated the safety and efficacy of Geneveve™ to treat vaginal laxity and sexual function in women following childbirth In 186 participants who were treated with this device, vaginal laxity improved in 43.5% participants in the treatment arm and in 19.6% of the sham group . Although there were no serious adverse events reported, the study was not powered to detect serious adverse events .…”
Section: Discussionmentioning
confidence: 99%